ReGAE 12: preventing glaucoma blindness in the Caribbean through implementation of the Moorfields Safer Surgery System and skills transfer from the UK to Trinidad and Tobago - Murray D (Dove Medical Press, 2018)
Desirée Murray,1,2 Peter Shah2–5 1Department of Clinical Surgical Sciences, The University of the West Indies, St Augustine, Trinidad and Tobago, West Indies; 2Birmingham Institute for Glaucoma Research, Institute of Translational Medicine, Birmingham, UK; 3University Hospitals Birmingham NHS Foundation Trust, Birmingham, UK; 4University College London, London, UK; 5Centre for Health & Social Care Improvement, School of Health & Wellbeing, University of Wolverhampton, Wolverhampton, UK Objective: The objective of the study was to present evidence of successful skills transfer of the Moorfields Safer Surgery System (MSSS) from the UK to Trinidad and Tobago and the safety and efficacy of this technique.Methods: Hospital-based retrospective, consecutive, non-comparative case series study of 33 eyes (24 African-Caribbean patients; 16 male patients) with primary open-angle glaucoma undergoing trabeculectomy + mitomycin C (MSSS) by a single surgeon with UK Glaucoma Fellowship training. The clinical outcome measures included intraocular pressure (IOP), bleb morphology, postsurgical interventions, postoperative complications, and best-corrected visual acuity (BCVA) at the final follow-up.Results: All patients were self-identified as African-Caribbean. The median age was 56 years (range 34–79 years). The mean preoperative IOP on maximum tolerated medical treatment was 22.4 mmHg (SD=5.9 mmHg). With or without medication, IOP was ≤21 mmHg in 92.6% at 1 year and 87.5% at 5 years. At 1 year, IOP was ≤18 mmHg in 78%, ≤15 mmHg in 73% and ≤14 mmHg in 52%. Removal of scleral flap releasable suture(s) was performed in 84%, 5-fluorouracil injection(s) in 88% and bleb needling revision in 38%. The most common complication was early transient bleb leak (52%). No patient developed endophthalmitis, hypotony maculopathy, suprachoroidal hemorrhage, or malignant glaucoma. At the final follow-up, 91% had excellent or satisfactory bleb morphology, and 73% had equal or better BCVA.Conclusion: Skills transfer between different geographical and economic regions contributes to the prevention of avoidable blindness through disease control – one of the core strategies of the World Health Organization’s Vision 2020 initiative. In the Caribbean (Trinidad and Tobago), the MSSS was utilized by a surgeon with Glaucoma Fellowship training and achieved outcomes similar to best-published data. This success can be reproduced in other geographic locations. Keywords: glaucoma, trabeculectomy, mitomycin C, Caribbean, African Caribbean